Deteksi Dini Sebagai Upaya Preventif Hipertensi Dan Diabetes Mellitus Melalui Edukasi Sehat Lansia - Saputra, Panca Umar; Sarwanto, Sarwanto (LPPM STIKES Madani, 2024)
Hypertension and diabetes mellitus are the leading causes of frequent and increasing public health problems. Early diagnosis of health conditions is crucial to better controlling the disease process. Early detection enables early intervention to slow or prevent disease progression and death. This activity aims to measure the knowledge of the elderly through health education related to the early detection of hypertension problems and the risk of developing diabetes mellitus. The activity was carried out in August 2023 at Dukuh Nglengis, Sitimulyo sub-district. Kapanewon Piyungan Bantul Regency has 68 elderly people. Family history of hypertension, age data, history of diabetes mellitus, and elderly knowledge using a questionnaire filled out by participants. The results of the pre-test show 32 respondents (47.06%) with poor knowledge. It is important to prioritize early detection as a factor in increasing public awareness, increasing access to health services, and improving health facilities for individuals and communities. Early detection programs are important as a strategy to improve knowledge about public health issues, including hypertension and diabetes mellitus.